Stop Diam, Saatnya Peduli Kekerasan Seksual dan Perundungan Melalui Pendidikan Karakter SMKN 1 Mojosongo: Penelitian - Eny Lintang Suryani; Erlita Andriyani; Eva Aulia Savira; Fajar Dwi Santosa; Dwi Imroatus Sholikah (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Sexual violence and bullying in educational settings are social problems that seriously impact the psychological, social, and academic development of students. Lack of understanding, permissive attitudes, and a culture of silence are factors that reinforce the continuation of these behaviors. The implementation of this activity aims to increase students' awareness, knowledge, and concern regarding the issues of sexual violence and bullying through strengthening educational character. The methods used include educational outreach, presentation of material using presentation media, presentation of educational videos, interactive discussions, and evaluation through pretests and posttests. The results of the activity showed a significant increase in students' understanding regarding the forms, impacts, and efforts to prevent sexual violence and bullying. In addition, there was a change in attitude marked by increased courage of the students educated to express concern, reject acts of violence, and report cases that occur in the school environment. This activity proves that character education is effective as a preventive approach in building a safe, inclusive, and equitable school culture.